2008
DOI: 10.1007/s00244-007-9124-z
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pollutants and Stable Isotopes in Resident and Migrant Passerine Birds from Northwest Michoacán, Mexico

Abstract: Although concentrations of organochlorine compounds (OCs) in birds from most of the United States and Canada have decreased over the last 30 years, there is still concern that migrant birds might be exposed to elevated concentrations of OCs during migration in Latin America. The Lerma-Chapala Basin in west-central Mexico is an important migration corridor and wintering area for many species. The objectives of this study were to assess if resident and migrant birds wintering in western Michoacán, Mexico accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Also, other studies have shown that some migratory birds use more nutrients acquired in their breeding grounds for egg production and accumulate more contaminants from the breeding grounds in their eggs . In a recent study, we showed that some passerine migrant birds, which likely nest in northern latitudes in the United States and southern Canada, appeared to have slightly greater DDE residues than passerine resident species from western Michoacán, Mexico . Thus, we assumed that the DDE concentrations observed in carcass and eggs in these reviewed studies reflected local acquisition rather than distant sources.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Also, other studies have shown that some migratory birds use more nutrients acquired in their breeding grounds for egg production and accumulate more contaminants from the breeding grounds in their eggs . In a recent study, we showed that some passerine migrant birds, which likely nest in northern latitudes in the United States and southern Canada, appeared to have slightly greater DDE residues than passerine resident species from western Michoacán, Mexico . Thus, we assumed that the DDE concentrations observed in carcass and eggs in these reviewed studies reflected local acquisition rather than distant sources.…”
Section: Discussionmentioning
confidence: 79%
“…It has been hypothesized for many years that North American migrant birds wintering in Latin America acquire contaminants such as DDE in their wintering areas and bring them back to their breeding grounds [27]. However, this hypothesis has been difficult to confirm and has been refuted by various studies [27][28][29][30][31][32][33][34]. Also, other studies have shown that some migratory birds use more nutrients acquired in their breeding grounds for egg production and accumulate more contaminants from the breeding grounds in their eggs [35,36].…”
Section: Annual and Latitudinal Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, Mora et al (2011) reportaron la presencia de DDE en huevos de halcón aplomado (Falco femoralis septentrionalis) colectados en áreas de anidación de Chihuahua (7.85 µg/g base lipídica) y Veracruz (5.51 µg/g), aunque el grosor del cascarón no mostró signos de adelgazamiento debido al DDE. Por otro lado, aves paseriformes residentes colectadas en zonas adyacentes al lago de Chapala en Michoacán (Mora 2008), mostraron concentraciones máximas de DDE de hasta 12 µg/g, mientras que aves migratorias presentaron concentraciones de DDE de hasta 0.01 µg/g. Este estudio indicó una posible fuente local (drenaje pluvial) de plaguicidas.…”
Section: Residuos En Fauna Silvestreunclassified